Reversible Fetal Renal Impairment following Angiotensin Receptor Blocking Treatment during Third Trimester of Pregnancy: Case Report and Review of the Literature - Tal Saar; Lorinne Levitt; Hagai Amsalem (Case Reports in Obstetrics and Gynecology)
Background. Late pregnancy usage of angiotensin converting enzyme inhibitors (ACE-I) and angiotensin II receptor blockers (ARB) may cause severe oligohydramnios due to fetal renal impairment. Affected neonates will often suffer from fatal, renal, and respiratory failure. Case. A 39-year-old multigravida admitted due to anhydramnios secondary to valsartan (ARB) exposure at 30 weeks’ gestation. Following secession of treatment amniotic fluid volume returned to normal. Delivery was induced at 34 weeks’ gestation following premature rupture of membranes and maternal fever. During the two-year follow-up, no signs of renal insufficiency were noted. Conclusions. This description of reversible fetal renal damage due to ARB intake during pregnancy is the first to show no adverse renal function in a two-year follow-up period. This case may help clinicians counsel patients with pregnancies complicated by exposure to these drugs.